Why do they follow influencers? Motivations and relationships of young law students with digital content - Mendoza Rivas, Natividad (2025)
Internet access has boosted the use of social networks, where influencers, recognized for their credibility and reach, generate cultural and social impact among young people, motivated by affinity, entertainment, and personal interests. The main objective of the article is to explore the motivations and forms of relationship in the following of influencers by young university students of UNMSM. The study was conducted using an interpretive and phenomenological approach, with a qualitative focus, aimed at understanding the experiences and meanings that students attribute to their social practices. A cross-sectional, non-experimental, and exploratory-descriptive design was employed. The data collection technique was structured interviews, applied to a sample of eleven law students from the National University of San Marcos (Class of 2025). The data were processed using Atlas.ti software, employing open, axial, and selective coding. Confidentiality, informed consent, and adherence to ethical principles were guaranteed throughout the research process. The study shows that law students at UNMSM follow influencers for identification, informational interest, academic utility, entertainment, and emotional connections. They value authenticity, charisma, and critical content. Furthermore, they establish different types of relationships: from parasocial bonds of companionship and emotional support to relationships based on empathy and social influence. Distant stances and ambivalent relationships marked by the tension between entertainment and the negative effects of excessive social media use were also observed. Overall, following and engaging with influencers reveals complex dynamics that integrate personal, cognitive, and affective dimensions.